'Getting our voices out there': acceptability of a mental health participation programme for young people with out of home care experience in Australia. (11th October 2019) - Rafeld, Jessie; Moeller-Saxone, Kristen; Cotton, Sue; Rice, Simon; Monson, Katherine; Harvey, Carol; Herrman, Helen
Abstract: Youth with experience of out-of-home-care (OoHC) typically have poorer mental health than their peers in the general population, and lack opportunities to contribute to service planning. Promoting mental health through leadership training may improve young people's mental health and facilitate system change. The Bounce Project is a pilot youth-leadership mental health training programme co-designed with young people who have experienced OoHC. In this study, we evaluated the Bounce Project from the young people's perspectives to explore the acceptability, successes and limitations of the training to promote the participant's mental health and their contribution to system level change. Thirteen young people aged 18–26 years old who had experienced OoHC and participated in the Bounce Project were interviewed. Semi-structured interviews were conducted and thematically analysed. Four major themes were thereby identified: making their mark; opportunities for growth; redefining roles and pitfalls of research participation. Participants valued the opportunity to have their voices heard, participate in research and learn about mental health. Perceived negative aspects included infrequent participation opportunities, interpersonal difficulties and frustration about the limitations of research including pressure to recruit and restrictive deadlines. Participating in the Bounce Project was a mostly positive experience, but young people also encountered barriers to meaningful participation. Youth with lived experience need more avenues to participate in research and leadership, but research programmes require specific designs that take into consideration the needs of participants and create opportunities for effective and meaningful participation.